2014
DOI: 10.1155/2014/318569
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Predictors of Increasing Waist Circumference in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study

Abstract: Type 2 diabetes mellitus (type 2 DM) has become a disease of public health concern worldwide. Obesity and elevated blood pressure have been shown to be comorbidities of type 2 DM. In this cross-sectional study in Tamale, Ghana, we determined the prevalence of abdominal obesity among type 2 DM patients. Furthermore, we examined the demographic, clinical, and anthropometric predictors of increasing waist circumference in this population. Three hundred type 2 DM patients attending the outpatient diabetes clinic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
3
4
1
Order By: Relevance
“…The prevalence of hypertension in this study (27%) is higher than the 19% reported by Mogre et al 30 among patients with type 2 diabetes in Tamale, Ghana, but lower than the 54.2% among patients with diabetes from Benin City, Nigeria. 31 Studies from Cameroon 10 and Kenya 11 also reported higher prevalence of hypertension at 66.4% and 50%, respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of hypertension in this study (27%) is higher than the 19% reported by Mogre et al 30 among patients with type 2 diabetes in Tamale, Ghana, but lower than the 54.2% among patients with diabetes from Benin City, Nigeria. 31 Studies from Cameroon 10 and Kenya 11 also reported higher prevalence of hypertension at 66.4% and 50%, respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…The results of this study indicated that absence of truncal obesity was an independent predictor of A1C < 7%. This finding concurs with other studies [41,42]. Mogre et al [41] in a cross-sectional study of T2D patients from Tamale, Ghana found a positive correlation between waist circumference and fasting blood glucose.…”
Section: 6%supporting
confidence: 93%
“…The most important factor in valuing this study was that almost all of the 1214 diabetics were treated by the authors. In this research there was a positive, significant correlation between WCs and ages of the diabetics as seen in the literature [19] [20]. In multiple linear regression models, age appeared to be a risk factor for WC.…”
Section: Discussionsupporting
confidence: 78%